Трамп, Твиттер и фейковые новости (Trump, Twitter and Fake News) - Munadhil Abdul Muqsith; Rizky Ridho Pratomo; Valerii L Muzykant (Jurnal Cita Hukum, 2021)
This study aims to provide rationality regarding Donald Trump as a fake news aggregator. Donald Trump's leadership from 2017-2020 is controversial and created a massive wave of fake news. As a populist leader, he often issued statements that confused the public during his reign, causing people's trust in the Trump administration to decline. He made the statement not only on national television but also on social media. Social media is the right political communication funnel for any populist leader when it comes to audience reach. Donald Trump is an active user especially on Twitter and uses it to spread misinformation and disinformation to spread what he calls as a truth. Many statements make Donald Trump worthy of being called a fake news aggregator. This study uses a qualitative approach with the content analysis method. Thirty-two samples of Donald Trump's hoax statements that were examined found that the hoaxes spread by him were not limited to just one topic. This research has both theoretical and practical significance. From a theoretical point of view, this research contributes to the development of literature regarding the relationship between hoaxes and populist leaders. In practical terms, this literature contributes to understanding the characteristics of populists and how social media is used as a funnel to spread hoaxes.Keywords: Hoax; Donald Trump; Populism; social media; TwitterTrump, Twitter and Fake NewsAbstrakPenelitian ini bertujuan untuk memberikan rasionalitas terkait Donald Trump sebagai fake news aggregator. Kepemimpinan Donald Trump pada periode 2017-2020 ini sangat kontroversial dan menciptakan sebuah gelombang fake news yang masif. Sebagai seorang pemimpin populis, dalam masa pemerintahannya, tak jarang dia mengeluarkan pernyataan yang menimbulkan kebingungan kepada masyarakat sehingga menyebabkan turunnya kepercayaan rakyat terhadap pemerintahan Donald Trump.Pernyataan itu dia lontarkan tidak hanya di media televisi nasional, tetapi juga media sosial. Bahkan, apabila berbicara jangkauan audience, media sosial menjadi corong komunikasi politik yang tepat bagi setiap pemimpin populis. Donald Trump merupakan pengguna aktif media sosial, khususnya Twitter. Donald Trump memanfaatkannya untuk menyebarkan misinformasi dan disinformasi untuk menyebarkan kebenaran versi miliknya. Ada banyak pernyataan yang membuat Donald Trump layak disebut sebagai fake news aggregator. Studi ini menggunakan pendekatan kualitatif dengan metode analisis konten. Sebanyak tiga puluh dua sampel pernyataan Donald Trump dikaji. Penulis menemukan bahwa berita bohong yang disebarkan olehnya tidak terbatas hanya satu topik semata. Penelitian ini memiliki signifikansi teoritis dan praktis. Dari segi teoritisnya, penelitian ini berkontribusi terhadap perkembangan literatur terkait hubungan antara hoaks dan pemimpin populis. Dalam segi praktisnya, literatur ini menjadi sumbangan pemikiran untuk memahami lebih lanjut karakteristik populis dan bagaimana media sosial digunakan sebagai corong untuk menyebarkan hoaks. Kata Kunci: Hoaks; Donald Trump; Populisme; Media Sosial; Twitter Трамп, Твиттер и фейковые новости АннотацияЭто исследование направлено на то, чтобы дать разумное представление о Дональде Трампе как агрегаторе фейковых новостей. Руководство Дональда Трампа в период 2017-2020 годов было очень спорным и вызвало массовую волну фейковых новостей. Как лидер популистов во время своего правления он часто делал заявления, которые вызывали замешательство у общественности, вызывая снижение доверия людей к правлению Дональда Трампа. Эти заявления он делал не только по национальному телевидению, но и в социальных сетях. Фактически, когда дело доходит до охвата аудитории, социальные сети являются правильной воронкой политической коммуникации для любого лидера популистов. Дональд Трамп - активный пользователь социальных сетей, особенно Твиттера. Дональд Трамп использует его для распространения недостоверной информации и дезинформации, чтобы распространить свою версию правды. Есть много заявлений, которые делают Дональда Трампа достойным называться агрегатором фейковых новостей. В этом исследовании используется качественный подход с методом контент-анализа. Были изучены 32 образца заявлений Дональда Трампа. Автор считает, что распространяемые им фейковые новости не ограничиваются одной темой. Это исследование имеет как теоретическое, так и практическое значение. С теоретической точки зрения, это исследование способствует развитию литературы о взаимоотношениях между обманом и популистскими лидерами. На практике эта литература является вкладом в дальнейшее понимание характеристик популистов и того, как социальные сети используются в качестве канала для распространения лжи.Ключевые слова: обман; Дональд Трамп; популизм; социальные сети; Твиттер